Strategic Planning Model to Increase Quality Basic School Education by 2020 - Yapandi Yapandi (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
This paper presents the reality of educational institutions that is, the weakening of the quality and quality of education in general and especially in elementary schools. This is the result of a study involving institutional boards, school committees, school managers (Principals, Vice Deans, Teachers and Program Coordinators) The main issue of this study is "What is the Future Model for Primary School Activity and Quality Program Plans 2020, Expected by determining the instruments and indicators of future success and on the implementation of the BOS model, compiled with data-based self-evaluation (EDS) through preliminary studies, establishing model instruments, targets, performance indicator programs, and personnel based on eight education standards for understand the strengths and weaknesses and provide operational, systematic, work steps according to achievement indicators, so that the model of BOS with the Strategic Planning Model approach to improve the quality of primary school education in 2020.